ANALISIS PENGEMBANGAN KURIKULUM DI LEMBAGA KURSUS UNGGULAN BAHASA ARAB (KUBA) KOTA MALANG - Mimi, Hermiwati (AL MURABBI, 2025)
This study aims to analyse curriculum development at the Arabic Language Excellence Course (KUBA) Malang City. The research used a qualitative method with a case study approach. Data were obtained through semi-structured interviews with Ustadz Ahmad Ubaidillah as the director of KUBA, as well as documentation in the form of teaching materials, learning media, and evaluation. Data analysis was conducted using the theory of Miles, Huberman, and Saldana, through the steps of data condensation, narrative presentation, and verification of conclusions. The results showed that KUBA developed a modern technology-based curriculum with an interactive learning approach. Innovations include the use of animated videos, educational games based on digital flashcards, and online quizzes. The curriculum also integrates the book Arabiyah Baina Yadaik which is relevant to local learning needs. Evaluations are conducted regularly to ensure the curriculum remains relevant and effective, with success measured through web-based exams and feedback from teachers. The findings underscore KUBA's commitment to creating Arabic language learning that is engaging, applicable, and in line with the demands of the digital age.